Effects of socio - economic status, school type and gender on pupils achievement in core subjects areas at the junior secondary school level in Rivers state (2012)
" Educators in Nigeria are relentlessly concerned about the need to improve learners’ academic achievement in core subject areas especially in Mathematics, English Language, Science and Social Studies. This is not only because a higher achievement in these core subjects lay foundation for technical skills, social orientation, numerical skills and skills in written and oral communication which are in short supply, but also because higher achievement is particularly valued in a society which sets high premium on academic success as the panacea ' for entrance into more prestigious occupation. This problem may not exist without some causes. This study therefore looked into some factors (school type, gender of the learner, socioeconomic background of a child and school environmental factors) as they affect academic achievement of learners. Survey design was adopted for the study. Proportionate random sampling technique was used to select 17 private and 17 public schools in three Local Government Areas (Obio- Akpor, Port-IIarcourt and Eleme) in Rivers State. In each school selected, 20 students (10 who attended private alongside 10 students who attended public schools) were chosen. In all 34 schools, 680 students (368 males and 312 females) participated in the study. Six valid and reliable instruments developed by the researchers were used to generate information for the study (Integrated Science Achievement Test (ISAT), Social Studies Achievement Test (SSAT), English Language Achievement Test (ELAT), Mathematics Achievement Test (MAT), Students Socio-Economic Background Questionnaire (SSEBQ) and School Environment Assessment Checklist (SEAC). The ISAT, SSAT, ELAT, and MAT were developed to measure student achievement in these subject areas. Their reliability coefficients kuder Richardson (KR20) were 0.81, 0.79, 0.76, and 0.82 for Integrated Science, Social Studies, English Language, and Mathematics respectively. The data was analyzed using descriptive and inferential statistics (frequency, percentages and t-test and ANOVA.) "